2012
DOI: 10.1021/nl301071n
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Exciton–Phonon Interaction in Two-Dimensional Colloidal CdSe Nanosheets

Abstract: We study the electronic structure of ultrathin zinc-blende two-dimensional (2D)-CdSe nanosheets both theoretically, by Hartree-renormalized k·p calculations including Coulomb interaction, and experimentally, by temperature-dependent and time-resolved photoluminescence measurements. The observed 2D-heavy hole exciton states show a strong influence of vertical confinement and dielectric screening. A very weak coupling to phonons results in a low phonon-contribution to the homogeneous line-broadening. The 2D-nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

50
403
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(457 citation statements)
references
References 42 publications
50
403
3
Order By: Relevance
“…Therefore, quantum confinement along lateral dimensions is expected to be very weak in these NPLs since the lateral size is much larger than the size (∼5À7 nm) of the first exciton. 15,25 Previously, Dubertret et al demonstrated that addition of a polar solvent such as ethanol into the solution of the NPLs, which is dissolved in apolar solvents (e.g., hexane and toluene), stacks the NPLs on top of each other, resulting in column-like assemblies. 19 When ethanol is introduced, NPLs tend to minimize their surface energy by drawing away ethanol since ethanol is an antisolvent for the ligands (oleic acid) of the NPLs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, quantum confinement along lateral dimensions is expected to be very weak in these NPLs since the lateral size is much larger than the size (∼5À7 nm) of the first exciton. 15,25 Previously, Dubertret et al demonstrated that addition of a polar solvent such as ethanol into the solution of the NPLs, which is dissolved in apolar solvents (e.g., hexane and toluene), stacks the NPLs on top of each other, resulting in column-like assemblies. 19 When ethanol is introduced, NPLs tend to minimize their surface energy by drawing away ethanol since ethanol is an antisolvent for the ligands (oleic acid) of the NPLs.…”
Section: Resultsmentioning
confidence: 99%
“…Multiexponential decay (three or four exponential decay functions) in the NPLs was also previously observed. 9,15,26 Figure 3c depicts the amplitude-averaged photoluminescence lifetimes of the NPLs as a function of total added ethanol amount (see Figure S3 for the individual lifetime components). The NPLs have a ∼3.38 ns average photoluminescence lifetime before stacking is induced, which is in accordance with the photoluminescence lifetime of the 4 ML CdSe NPLs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such NPLs exhibit electronic and optical properties that differ from those for QDs, such as much narrower absorption and PL bands (FWHM < 10 nm), a giant oscillator strength, lower thresholds for amplified spontaneous emission and higher optical gain saturation. [33][34][35] However, the synthesis of heteronanostructures based on such nanoplatelets is limited to the preparation of CdSe-CdS or CdSe-CdZnS nanoparticles. [36][37][38] Recently, we have shown that overgrowth of CdSe NPLs with CdS in the presence of acetate species results in the formation of NPLs with a "corewings" architecture.…”
Section: Introductionmentioning
confidence: 99%